TRANSFORMASI PEMBELAJARAN PENDIDIKAN PANCASILA MELALUI GAMIFIKASI DIGITAL: PENGARUH MEDIA WORDWALL TERHADAP MOTIVASI BELAJAR PESERTA DIDIK KELAS IV MIN 3 LAMPUNG SELATAN - Vita Mulyasari; Dayu Rika Perdana; Sheren Dwi Oktaria; Muhammad Nurwahidin (STKIP Subang, 2026)
The problem in this study is the low learning motivation of grade IV students in the Pancasila Education subject at MIN 3 Lampung Selatan. which is influenced by the lack of student activity and the use of learning media that is not optimal so that learning tends to be monotonous. This study aims to determine the influence of learning transformation of Pancasila Education through digital gamification using Wordwall media on the learning motivation of grade IV students. The research method used is (quasi experiment design) with a research design that uses non-equivalent control group design. The research population was 111 students, with a sample of 55 students divided into experimental classes and control classes. Data collection was carried out through pretest and posttest tests, questionnaires, observations, and documentation. The hypothesis test used simple linear regression with a result of 0.00 < 0.05, so that Ho was rejected and Ha was accepted. The results of the study showed that the use of digital gamification-based Wordwall media had a positive effect on the learning motivation of students in Pancasila Education subjects at MIN 3 Lampung Selatan.